Sonothromblysis in Combination with Thrombolytic Drugs in a Rabbit Model Using MRI-Guidance - Damianou, Christakis A.; Mylonas, Nicos; Ioannides, Kleanthis (My University, 2013)
The potential of MRI-guided focused ultrasound (MRgFUS) combined with the thrombolytic drug recombinant tissue plasminogen activator (rt-PA), to dissolve clots in the carotid of a New Zealand rabbitin vivois evaluated. A spherically-focused transducers of 5 cmdiameter; focusing at10 cmand operating at 1 MHz was used. A pulsed ultrasound protocol was used that maintains a tissue temperature increase of less than 1℃ in the clot (called safe temperature). MRgFUS has the potentials to dissolve clots that are injected in the carotid of rabbits in vivo. It was found that the time needed for opening the carotid artery using ultrasound and rt-PA was decreased compared to just using rt-PA. The proposed protocol was monitored using Magnetic Resonance Angiography (MRA) every 1 min.
Keywords: Ultrasound; MRI; Stroke; Thrombolysis